Defect-induced enhanced photocatalytic activities of reduced α-Fe2O3 nanoblades. (10th June 2016) - Feng, Honglei; Wang, Yiqian; Wang, Chao; Diao, Feiyu; Zhu, Wenhui; Mu, Peng; Yuan, Lu; Zhou, Guangwen; Rosei, Federico
Abstract: Bicrystalline α -Fe2 O3 nanoblades (NBs) synthesized by thermal oxidation of iron foils were reduced in vacuum, to study the effect of reduction treatment on microstructural changes and photocatalytic properties. After the vacuum reduction, most bicrystalline α -Fe2 O3 NBs transform into single-layered NBs, which contain more defects such as oxygen vacancies, perfect dislocations and dense pores. By comparing the photodegradation capability of non-reduced and reduced α -Fe2 O3 NBs over model dye rhodamine B (RhB) in the presence of hydrogen peroxide, we find that vacuum-reduction induced microstructural defects can significantly enhance the photocatalytic efficiency. Even after 10 cycles, the reduced α -Fe2 O3 NBs still show a very high photocatalytic activity. Our results demonstrate that defect engineering is a powerful tool to enhance the photocatalytic performance of nanomaterials.